BLENDED LEARNING AS TOOL OF INTENSIFICATION OF EDUCATIONAL PROCESS IN TEACHING DISCIPLINE «METHODS AND TECHNOLOGIES OF DISTANCE LEARNING» (Journal of Information Technologies in Education (ITE), 2015)
The problem of constructing a new model of training process of future and highly competitive professionals in high school arises due to the global process of society informatization and the involvement of ICT in all spheres of human activity, including the educational process of high school.     In conditions of Ukraine integration into the European educational space, the significant changes in the curriculum of training of professionals are happened, that the number of classroom training hours is reduced and the number of hours of self-study training is increasing. However,self-study learning raises many difficulties as for students and teachers, for example, the lack of guidance on the tasks for independent work, lack of consultation of teachers, insufficiently formed students’ skills of self-education and so on. These problems adversely influenced on the quality of future professionals in high school.     Thus, there is need to implement blended learning in educational process for solving a number of problems. Thus, the model of the educational process with the use of blended learning is suggested, based on the analysis of the scientific literature in training future professionals, the results of international research papers and trainers. The interactions between elements of the model are established and their importance in the educational process as a whole is emphasized.The proposed model was tested during the learning process of the course "Methods and Technologies of Distance Learning" for students of Master’s degree, specialty "Computer Science" Faculty of Physics, Mathematics and Computer Science, Kherson State University.
Keywords: blended learning; intensification; information and communication technologies; electronic educational-methodical complex; distance learning; distance learning system «Kherson Virtual University»